Implementation of Normative Intelligence Policy In Immigration View - Olyvia Sindiawaty; Mercy Marvel (Journal of Law and Border Protection, 2019)
Intelligence Policy has often been heard in the realm of law, especially with government agencies held in Indonesia. One of them is the immigration agency, which is under the auspices of the Ministry of Law and Human Rights. The implementation of the policy is still minimal, although in fact it is contained in article 1 of Law No. 6 of 2011 number 30, as well as article 74. There are still many that need to be addressed, both in the applicable legal rules and with implementation in the field. The fact that sometimes the Immigration Officer is sometimes mixed in its own definition of intelligence and oversight. Are they the same or different and how to distinguish the two. Recognizing the fact that immigration is increasingly compacted by traffic activities in and out of foreigners and citizens and their supervision, a qualified intelligence is needed in maintaining the upholding of the country's sovereignty. It is an obligation, especially for immigration to safeguard the country as stated in the immigration function, is part of the affairs of the state government in providing Immigration services, law enforcement, state security, and community welfare development facilitators. Therefore, immigration should take part in enforcing supervision and security of the state in the field of law. Immigration intelligence which is under the auspices of the Directorate of Intelligence and immigration enforcement should need to be developed more thoroughly as a whole. So, it is hoped that in the future the Indonesian state will have total sovereignty over the country and its own people.